2021
DOI: 10.3389/fimmu.2020.602070
|View full text |Cite
|
Sign up to set email alerts
|

Review: Occurrence and Distribution of Galanin in the Physiological and Inflammatory States in the Mammalian Gastrointestinal Tract

Abstract: Galanin (GAL) is a broad-spectrum peptide that was first identified 37 years ago. GAL, which acts through three specific receptor subtypes, is one of the most important molecules on an ever-growing list of neurotransmitters. Recent studies indicate that this peptide is commonly present in the gastrointestinal (GI) tract and GAL distribution can be seen in the enteric nervous system (ENS). The function of the GAL in the gastrointestinal tract is, inter alia, to regulate motility and secretion. It should be note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 100 publications
1
19
0
Order By: Relevance
“…However, nonneural expression of GAL-like immunoreactivity has been reported in several other tissues and cells: fibroblast cell lines (Yamamoto et al 2014); primary epidermal keratinocytes (Lee et al 2017); macrophage-like cells of the synovial membrane (Wu et al 2004); fibroblast-like cells in skin during the formation of granulation tissue (Yamamoto et al 2011); osteoprogenitor cells, osteoblasts, and chondrocytes of the hypertrophic zone during rib fracture repair (McDonald et al 2003); and blood vessels, hair follicles, and sweat glands (Kofler et al 2004; Lang et al 2007). Moreover, previous studies suggested that GAL is involved in the regulation of inflammatory processes (Koller et al 2017; Koller et al 2019; Brzozowska and Calka 2021; Martinelli et al 2021). Earlier studies have speculated about an application of GAL in tissue regeneration (McDonald et al 2003; Yamamoto et al 2011; Yamamoto et al 2014), and one study applied GAL injections to promote calvarial bone formation via an injection strategy (McDonald et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nonneural expression of GAL-like immunoreactivity has been reported in several other tissues and cells: fibroblast cell lines (Yamamoto et al 2014); primary epidermal keratinocytes (Lee et al 2017); macrophage-like cells of the synovial membrane (Wu et al 2004); fibroblast-like cells in skin during the formation of granulation tissue (Yamamoto et al 2011); osteoprogenitor cells, osteoblasts, and chondrocytes of the hypertrophic zone during rib fracture repair (McDonald et al 2003); and blood vessels, hair follicles, and sweat glands (Kofler et al 2004; Lang et al 2007). Moreover, previous studies suggested that GAL is involved in the regulation of inflammatory processes (Koller et al 2017; Koller et al 2019; Brzozowska and Calka 2021; Martinelli et al 2021). Earlier studies have speculated about an application of GAL in tissue regeneration (McDonald et al 2003; Yamamoto et al 2011; Yamamoto et al 2014), and one study applied GAL injections to promote calvarial bone formation via an injection strategy (McDonald et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While the mechanism by which GAL regulates tissue regeneration is currently unknown, it has been shown that GAL affects cardiomyoblasts through the FoxO1 pathway (Martinelli et al 2021), a possible candidate pathway as FoxO family members have been implicated in the regulation of osteoprogenitors, osteoblasts, and osteoclasts (Alharbi et al 2018; Ma et al 2020). In addition, anti-inflammatory effects of GAL have been indicated in animal models with chronic inflammatory diseases (Talero et al 2006; Talero et al 2007; Brzozowska and Calka 2021). These data suggest that the anti-inflammatory and regenerative effects of GAL will restore physiologic periodontal tissue homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Galanin, an important neurotransmitter, has also been shown to have neuroprotective effects in both the central and peripheral nervous systems [ 9 ]. Meanwhile, GAL has been shown to be involved in the differentiation of mucosal-type mast cell (MMCs) in vivo, while In the same study, the authors suggest that GAL released from the submucosal neurons may contribute to the differentiation and proliferation of MMC during enteritis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Galanin (GAL) was first isolated in 1983 [ 9 ]. The presence of GAL has been confirmed both in the central and peripheral nervous system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation